2007
DOI: 10.1038/sj.npp.1301305
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine and Serotonin Receptor Binding and Antipsychotic Efficacy

Abstract: The relationship between clinically effective antipsychotic drug dosage and binding affinity to cloned dopamine (DA) and serotonin receptor subtypes was analyzed in an effort to elucidate the contribution of individual receptor subtypes to medication response. Clinically effective dose and binding affinity to D 2 DA receptor were modestly correlated for typical antipsychotic medications (r ¼ 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(77 citation statements)
references
References 49 publications
3
74
0
Order By: Relevance
“…Clozapine is a multireceptor acting AP; it has antagonistic activity on dopaminergic receptors, with a higher affinity at the D1 and D4 receptors than at the D2 receptors, also binding to the extra-striatal D3 receptors. Clozapine has also antagonistic activity at the 5-HT1A, 5-HT2A, 5-HT2C, and 5-HT3 receptors [75]. Our results are in agreement with previous reports indicating that clozapine is the atypical AP that more frequently is associated with seizures [17], or involving seizures/lowered seizure threshold associated with its use [78,79].…”
Section: Clozapinesupporting
confidence: 83%
See 2 more Smart Citations
“…Clozapine is a multireceptor acting AP; it has antagonistic activity on dopaminergic receptors, with a higher affinity at the D1 and D4 receptors than at the D2 receptors, also binding to the extra-striatal D3 receptors. Clozapine has also antagonistic activity at the 5-HT1A, 5-HT2A, 5-HT2C, and 5-HT3 receptors [75]. Our results are in agreement with previous reports indicating that clozapine is the atypical AP that more frequently is associated with seizures [17], or involving seizures/lowered seizure threshold associated with its use [78,79].…”
Section: Clozapinesupporting
confidence: 83%
“…Compared with typical APs, it also binds with a lower affinity at the adrenergic (α1 and α2) and H1 histaminergic receptors [75,76]. We found that risperidone increases the incidence and the severity of the audiogenic seizures (Figs.…”
Section: Risperidonementioning
confidence: 84%
See 1 more Smart Citation
“…Mesoridazine has also been used as a drug itself. Mesoridazine and thioridazine possess affinity for the dopamine D 2 , D 3 , and D 4 receptors (Richtand et al, 2007), with mesoridazine showing somewhat greater affinity. After administration of thioridazine, total exposure to thioridazine is about 6-fold greater than the mesoridazine; however, it has been shown that the parent drug is vastly more protein-bound than the metabolite.…”
Section: Procainamidementioning
confidence: 99%
“…All approved antipsychotic medicines act, with respect to G-protein coupling, either as antagonists, inverse agonists or low efficacious partial agonists at the D2-like receptors. Moreover, their therapeutic active dose correlates with the occupancy at the D2 receptor (Akam and Strange, 2004;Burstein et al, 2005;Richtand et al, 2007).…”
Section: Introductionmentioning
confidence: 99%